The application of cyber-insurance in computer networks - Feng, Shaohan (Nanyang Technological University, 2020)
Due to the increasing complexity in the network attacks, perfectly securing the computer networks by relying solely on the security techniques might no longer be a sufficient and suitable solution. In this thesis, we adopt the cyber-insurance, i.e., an alternative means of cyber risk management, to manage the cyber risks due to the cyber attacks in computer networks. By enabling the transfer of the cyber risks from the computer networks to a third party, i.e., cyber insurer, cyber-insurance has been recognized as a promising and efficient approach to manage the cyber risks. Specifically, our three major research issues focus on three application scenarios of the cyber-insurance in computer networks, which are summarized as follows.